Β2-receptor agonists salbutamol and terbutaline attenuated cytokine production by suppressing ERK pathway through cAMP in macrophages. (June 2017) - Keränen, Tiina; Hömmö, Tuija; Moilanen, Eeva; Korhonen, Riku
Highlights: In general, ligand-β2 -receptor engagement activates ERK pathway. In this study, β2 -agonists inhibited TNF and MCP-1 production in macrophages. Inhibition of TNF and MCP-1 production was associated with attenuated ERK signaling. Suppression of ERK pathway was dependent on cAMP signaling. Abstract: β2 -receptor agonists are used in the treatment of inflammatory obstructive lung diseases asthma and COPD as a symptomatic remedy, but they have been suggested to possess anti-inflammatory properties, also. β2 -receptor activation is considered to lead to the activation of ERK pathway through G-protein- and cAMP-independent mechanisms. In this study, we investigated the effects of β2 -receptor agonists salbutamol and terbutaline on the production of inflammatory factors in macrophages. We found that β2 -receptor agonists inhibited LPS-induced ERK phosphorylation and the production of MCP-1. A chemical cAMP analog 8-Br-cAMP also inhibited ERK phosphorylation and TNF and MCP-1 release. As expected, MAPK/ERK kinase (MEK)1/2 inhibitor PD 0325901 inhibited ERK phosphorylation and suppressed both TNF and MCP-1 production. In conclusion, we suggest that β2 -receptor agonists salbutamol and terbutaline inhibit inflammatory gene expression partly by a mechanism dependent on cAMP leading to the inhibition of ERK signaling in macrophages. Observed anti-inflammatory effects of β2 -receptor agonists may contribute to the clinical effects of these drugs.